2009
DOI: 10.1515/cclm.2010.052
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum alkaline phosphatase and C-reactive protein in the United States National Health and Nutrition Examination Survey 2005–2006

Abstract: ALP is a marker of cardiometabolic risk, but it needs to be tested as part of a multivariate model in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
81
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 28 publications
12
81
3
Order By: Relevance
“…17,18 ALP has shown to be associated with CRP in this and other studies. 20 ALP levels may, therefore, partially reflect inflammation of hepatic origin because CRP is hepatically derived. In vascular disease, atherosclerosis is associated with inflammatory processes (reflected in raised CRP levels), and in advanced atherosclerotic plaque there is calcification and increased expression of ALP.…”
Section: Alp and Cvdmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 ALP has shown to be associated with CRP in this and other studies. 20 ALP levels may, therefore, partially reflect inflammation of hepatic origin because CRP is hepatically derived. In vascular disease, atherosclerosis is associated with inflammatory processes (reflected in raised CRP levels), and in advanced atherosclerotic plaque there is calcification and increased expression of ALP.…”
Section: Alp and Cvdmentioning
confidence: 99%
“…In vascular disease, atherosclerosis is associated with inflammatory processes (reflected in raised CRP levels), and in advanced atherosclerotic plaque there is calcification and increased expression of ALP. 20 Thus, inflammation may be a common link between ALP and CHD. Because proinflammatory cytokine is known to stimulate release of vWF from vascular endothelium, this may explain the association between ALP and endothelial dysfunction, although other pathways may be clearly involved.…”
Section: Alp and Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that TCZ injection reduced the level of ALP, which is a biochemical marker for bone and liverbiliary disorders as well as lapidated liver (15,16). Some studies reported that triazoles reduce ALP levels (6,12), while others claimed the opposite (17,18). The reduced level of ALP may be caused by bile duct hyperplasia observed in histopathological examination of our TCZ-treated samples.…”
Section: Resultsmentioning
confidence: 60%
“…These measurements are complementary: the patient's glucose measurements provide a picture of short-term glycemic control, whereas HbA1c reflects average glycemic control over the previous 3 months. 11 In a recently published literature-based Meta-analysis of studies assessing the associations of liver enzymes and CVD risk in participants recruited from approximately general populations, the results suggested a modest positive linear association between ALP activity and CVD risk. 12 The purpose of study was to investigate a possible correlation between raised ALP levels in type 2 diabetics and non-diabetics.…”
mentioning
confidence: 99%